1998
DOI: 10.2337/diacare.21.4.615
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of Motor Nerve Conduction Velocity to F-Wave Conduction Velocity in Diabetic Neuropathy

Abstract: Results suggest that the M/F ratio, which is influenced by the neuronal damages in the distal segment of peripheral nerves, is useful in the differential diagnosis of diabetic neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…We agree with the general observation of Rutkove et al 23 that the sural/radial amplitude ratio provides a sensitive electrodiagnostic test for axonal polyneuropathy (using, for our data, a cutoff ratio of 0.34 rather than their value of 0.40). As with other ratios recently proposed for the differential diagnosis of diabetic neuropathy, 15 it has the great advantage of not requiring adjustment for age and height using normal controls with strictly standardized technical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…We agree with the general observation of Rutkove et al 23 that the sural/radial amplitude ratio provides a sensitive electrodiagnostic test for axonal polyneuropathy (using, for our data, a cutoff ratio of 0.34 rather than their value of 0.40). As with other ratios recently proposed for the differential diagnosis of diabetic neuropathy, 15 it has the great advantage of not requiring adjustment for age and height using normal controls with strictly standardized technical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…We also determined the mean value, of the most abnormal, lower limb compound muscle action potential (CMAP) in each patient and control and compared the values between the two groups. Finally, the ratio of MNCV to minimum F‐wave latency (M/F), has previously been shown to be higher in diabetic neuropathics in comparison with controls [12]. We evaluated the potential value of this ratio in the diagnosis of LFSN, by comparison of means, utilizing the most abnormal lower limb nerve for each subject of each group.…”
Section: Methodsmentioning
confidence: 99%
“…8 Study done by Kimiko Ohgaki et al suggested that the ratio of motor conduction velocity to F wave conduction velocity is very useful in distinguishing diabetic neuropathy from other polyneuropathies. 9 The ratio of F wave amplitude to the associated M wave (F/M ratio) is a measure of proportion of motor neuron pool activated by antidromic stimulation. It helps in diagnosis of axonal neuropathy though not highly sensitive.…”
Section: Introductionmentioning
confidence: 99%